Differential Exposure to Borrelia spp. and Spotted Fever Group Rickettsia in Serbia and North Macedonia: A Comparative Study - Jakimovski, Dejan; Mateska, Sofija; Najdovska, Marija; Stamenkovska, Angela; Pavleva, Verica; Bosilkovski, Mile; Mijatović, Dragana; Simin, Verica; Bogdan, Ivana; Grujić, Jasmina; Simeunović, Milica; Vranješ, Miodrag; et al. (MDPI AG, 2025)
Several diseases caused by tick-borne pathogens, including Lyme borreliosis (LB) and spotted fever group rickettsioses, are endemic in the Balkan Peninsula, positioned between Central Europe and the Middle East. This cross-sectional study aimed to assess serological exposure to Borrelia spp. and spotted fever group Rickettsiae (SFGR) among individuals with recent tick bites and healthy controls in two Balkan countries-Serbia and North Macedonia. Serum samples from 223 participants were tested for anti-Borrelia and anti-SFGR IgG antibodies. SFGR exposure was significantly higher in tick-exposed individuals from Skopje (North Macedonia) compared to those from Novi Sad (Serbia) (30.9% vs. 8.0%; p = 0.003). In contrast, anti-Borrelia IgG was more frequently detected in Novi Sad, though differences did not reach statistical significance. The findings support a north-to-south gradient in Borrelia exposure and a reverse trend for SFGR, consistent with earlier studies and regional tick infection data. Given the high SFGR exposure and limited clinical reporting in North Macedonia, the results highlight the likelihood that tick-borne rickettsioses remain under-recognized. Additionally, Borrelia exposure in North Macedonia warrants further investigation. These findings emphasize the need for enhanced tick-borne disease surveillance, identification of endemic zones, and improved diagnostic and public health infrastructure in both countries.
Keywords: Balkans; Borrelia; North Macedonia; Rickettsia; Serbia; tick-borne diseases